Implementation of a Network Security System Against SYN Flood Attacks and Unauthorized Access Blocking Using Firewall Filtering in the IT Service Department of PT Pupuk Sriwidjaja Palembang - M. Syaiful Huda Mubarok (Jurnal Jaringan Komputer dan Keamanan, 2025)
The Information Technology Services Department of PT Pupuk Sriwidjaja (PUSRI) Palembang relies heavily on internet network access to support a wide range of operational activities and to provide Information Technology (IT) services for various departments within the company. However, internet access within the IT Services Department must be tightly regulated and secured. One of the network security mechanisms applied is the firewall filtering method. Firewall filtering is used to protect network systems from SYN Flood attacks, prevent unauthorized access, and block potential threats from hacker activities. The firewall filtering mechanism inspects all incoming TCP connections, opens or blocks network ports such as ports 22 and 80, and filters source IP addresses, port ranges, and suspicious traffic patterns. By implementing a network security system against SYN Flood attacks, the network becomes more stable and secure and can operate normally without concerns about SYN-based disruptions or other forms of illegal access.